EFFECTIVENESS OF ORAL OMEGA 3 IN REDUCING MUCOCUTANEOUS SIDE EFFECTS OF ORAL ISOTRETINOIN IN PATIENTS WITH ACNE VULGARIS - Zainab, Zarnab; Malik, Naveed Akhtar; Obaid, Shanza; Malik, Saqib; Aftab, Kanza; Mumtaz, Maimoona; Pervaiz, Alia; Syed, Zainab (Journal of Ayub Medical College Abbottabad, 2021)
Background: Acne vulgaris has been a common clinical condition. Due to. high prevalence and unclear etio-pathogenesis of acne vulgaris, large number of treatment options have been available across the globe. Limited work has been done to explore the options which may manage or prevent these adverse effects and improve the adherence to the prescribed medications. We therefore conducted this trial to look for effectiveness of oral omega 3 in reducing mucocutaneous side effects of oral isotretinoin in patients with acne vulgaris. Objective: To look for effectiveness of oral omega 3 in reducing mucocutaneous side effects of oral isotretinoin in patients with acne vulgaris. It was a randomized control trial conducted at Department of Dermatology Pak Emirates Military Hospital Rawalpindi. Ten months, June 2019 to May 2020. Methods. A total of 60 patients of acne vulgaris put on oral isotretinoin by consultant dermatologist were included in the study. Patients were randomized into groups by lottery method. Group A received the placebo along with oral isotretinoin while Group B received oral omega 3 in standard dose in addition to oral isotretinoin. Comparison was made in both the groups regarding common mucocutaneous side effects. Results Out of 60patients with acne vulgaris and put on isotretinoin included in the study, 26 (43.3%) received placebo in addition to isotretinoin while 34 (56.7%) received omega 3 in addition to isotretinoin. Forty (66.7%) patients were female while 20 (33.3%) were male. Cheilitis 35 (58.3%) was the commonest side effect followed by lip dryness 33 (55%). Application of chi-square test revealed that cheilitis, lip dryness and xerosis were significantly found in more patients who received placebo as compared to those who received omega 3 along with isotretinoin. Conclusion Mucocutaneous side effects were a very common finding among patients of acne vulgaris managed with isotretinoin. Cheilitis was the most reported mucocutaneous side effects among the target population. This RCT demonstrated that omega 3 was superior to placebo in order to prevent or manage cheilitis, xerosis or dry lips. Keywords: Acne vulgaris; Isotretinoin; Mucocutaneous; Omega 3